The Use of Physical Activity Mobile Apps Improves the Psychological State of Adolescents: A Randomized Controlled Trial - Adrián Mateo-Orcajada; Raquel Vaquero-Cristóbal; Lucía Abenza-Cano (Human Behavior and Emerging Technologies)
Mobile applications positively influence the practice of physical activity in adolescents, but the effect of this improvement on the psychological state and the addictive use of technologies in this population is unknown. For this reason, the aims of the present investigation were to establish the differences in psychological variables and problematic mobile phone use by adolescents after a 10-week intervention with mobile apps, according to gender and the different mobile applications used. A randomized controlled trial was conducted in Spain with 400 adolescents aged 12–16 years (mean age: 13.96±1.21 years old) whose physical activity level, satisfaction of competence, autonomy, and relatedness, life satisfaction, and addictive use of the mobile phone were measured. Two measurements were taken, with a 10-week intervention period in between. During the intervention, adolescents in the experimental group (EG) must use one of the selected mobile applications (Strava, Pacer, MapMyWalk, or Pokémon-Go) a minimum of 3 times per week, covering the distance indicated for each week. The use of the mobile applications was randomized for each class group, and an explanation was given to the adolescents prior to the start of the intervention. The results showed that EG showed a significant improvement in the psychological variables (p=0.003−0.036) compared to the control group and also a decreased problematic mobile phone use (p=0.004). Specifically, females in the EG increased autonomy (p=0.010), relatedness (p=0.019), and life satisfaction (p=0.020), while males improved relatedness (p=0.021) and competence (p=0.018). In addition, the different applications used could influence autonomy, relatedness, and problematic mobile phone use. To conclude, the use of mobile step trackers could be useful to maintain an adequate psychological state of the adolescent population without increasing the addictive or problematic use of these technologies.